2010
DOI: 10.3987/rev-09-665
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of New Catalytic Synthetic Methods for Nitrogen Heterocycles Based on Hydrogen Transfer Reactions

Abstract: This review summarizes a variety of synthetic methods for nitrogen heterocycles based on hydrogen transfer reactions catalyzed by transition metals in a past decade. Most of them employ iridium and ruthenium complexes as the catalysts and provide a versatile and environmentally benign synthetic methodology of various nitrogen heterocyclic compounds. Intermolecular cyclization reactions of amines with alcohols afford 5-7 membered alicyclic amines, quinolines, piperazines, indoles, quinoxalines, pyrroles, benzim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(40 citation statements)
references
References 60 publications
0
39
0
1
Order By: Relevance
“…Preliminary results on the oxidation of 1-phenylethanol (7a) to acetophenone (8a) using a variety of ruthenium hydride complexes such as RuH 2 (CO)- (4) and Ru(0) complexes such as Ru 3 (CO) 12 (5) and RuA C H T U N G T R E N N U N G (cod)A C H T U N G T R E N N U N G (cot) (6) are shown in Table 1. Complex 1 gave 8a in a low yield of 33% under toluene reflux conditions (entry 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary results on the oxidation of 1-phenylethanol (7a) to acetophenone (8a) using a variety of ruthenium hydride complexes such as RuH 2 (CO)- (4) and Ru(0) complexes such as Ru 3 (CO) 12 (5) and RuA C H T U N G T R E N N U N G (cod)A C H T U N G T R E N N U N G (cot) (6) are shown in Table 1. Complex 1 gave 8a in a low yield of 33% under toluene reflux conditions (entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…[7] Several transition metal complexes, such as Ru, [8] Rh, [9] Ir [10] and Au [11] complexes, in the presence of stoichiometric amounts of oxidizing agents have been extensively used as catalysts in the oxidation reactions. [12] Examples of the oxidizing agents are peroxides, PhIO, N-methylmorpholine N-oxide, 2,6-dimethoxybenzoquinone and K 2 S 2 O 8 . However, from both environmental and economic points of views, the use of stoichiometric amounts of oxidants is undesirable.…”
Section: Introductionmentioning
confidence: 99%
“…Thus pyrrolidines were formed by the intramolecular reaction of N-substituted 4-aminobutan-1-ols in the presence of 5mol %[RhH(PPh 3 ) 4 ] as the catalyst in boiling 1,4-dioxane.T he cascade reaction consists of dehydrogenative oxidation of the alcohol to an aldehyde,imine formation with an amine,and hydrogenative reduction of the imine to afford the N-substituted pyrrolidines 1a and 1b in 56 and 82 %yields,respectively [Eq. (1)].…”
Section: Annulation By N-alkylation Of Amines By Alcoholsmentioning
confidence: 99%
“…)hydrogen-transfer reactions, [3] Ru-, Ir-, and rare examples of Fe-based catalytic systems have shown excellent activity and selectivity in hydrogen-transfer annulations to deliver heterocyclic compounds.I n2 010, Yamaguchi et al reported ar eview article focusing on the construction of nitrogen-based heterocycles by transitionmetal-catalyzed hydrogen-transfer annulations. [4] In recent years,t his field has evolved in terms of catalyst and ligand design, and reaction conditions,t hus taking the place of conventional synthetic processes and receiving an overwhelming amount of attention. In this respect, there is need for ar eview article focused on the potential of catalytic hydrogen-transfer annulation strategies for the formation of heterocyclic scaffolds.H erein we highlight recent advancements in hydrogen-transfer annulations of alcohols with various nucleophilic partners,t hus leading to the formation of heterocyclic scaffolds.T his review material is organized into four different categories:a )N-alkylation of amines by alcohols,b )dehydrogenative amide formation from amines and alcohols,c )oxidative cyclization of alcohols,a nd d) annulation of unsaturated systems.…”
Section: Scope and Organization Of Reviewmentioning
confidence: 99%
“…5 The available routes to these heterocycles, whether through conventional, polar reactions 6 or by metal catalysis, 7 have certain limitations, such as the need for high temperatures or multiple steps. We present here a general method for the synthesis of diverse, highly substituted piperazines and related nitrogen heterocycles, starting from readily available building blocks.…”
mentioning
confidence: 99%